Liberalization reform and productivity growth in Indonesia: firm level evidence - Suatmi, Bernadetta Dwi (Curtin University, 2016)
This thesis examines the effect of trade reform on firm-level efficiency and productivity growth in four selected Indonesian manufacturing industries. The stochastic production frontier (SPF), Färe-Primont productivity index and econometric estimation are applied. Empirical results show that effects of trade reform variables vary across industries, across sub-periods, and across TFP and its components. Therefore, the government may need to consider the characteristics of firms in each industry when formulating current trade policies.